(untitled) (REMUNOM, 2025)
This article addresses the relationship between the positivist research paradigm and artistic expressions mediated by digital technologies. It analyzes how positivism, as an epistemological approach based on objectivity and the measurement of phenomena, dialogues or enters into tension with art, traditionally associated with subjectivity, expression and creativity. In addition, it discusses the role of technologies as mediators of this process, enhancing both production and academic research on art. Finally, it presents reflections on the limits and possibilities of positivist research in the artistic field in times of digital culture.